Nutrition Management in Elderly with Diabetes Mellitus: Literature Review - Eqlima Elfira; Bina Melvia Girsang; Franklin Asido Rossevelt (Talenta Publisher, 2022)
Diabetes often occurs in the elderly who have become a great social burden. The effects of diabetes are weakness, cognitive dysfunction which is closely related to the aging mechanism. Nutritional management is one of the therapeutic diets as the cornerstone of diabetes treatment based on healthy and wise dietary guidelines. The purpose of this study was to determine the nutritional management of the elderly in diabetes mellitus. The research method used is a literature review and to select studies using the PRISMA Checklist protocol and PICOS format To determine the articles to be reviewed from Googlescholar and PubMed, 15 articles were found that met the criteria indicating that nutritional management in the elderly with diabetes mellitus must consider the quality of health (health status, activity, functional and psychological status), nutritional intake (vitamins, minerals, and fiber), and changing eating habits by following a healthy diet.